2004
DOI: 10.1111/j.1447-0756.2004.00198.x
|View full text |Cite
|
Sign up to set email alerts
|

Germ cell tumors of the ovary: A clinicopathologic study of 121 cases from Nepal

Abstract: Mature teratoma is the most common germ cell tumor and accounts for 40.50% of all ovarian neoplasms. The high prevalence of germ cell tumors of the ovary found among patients who were hill natives needs to be explored further.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
17
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 10 publications
(13 reference statements)
6
17
2
Order By: Relevance
“…This was different to the findings of Sah et al 8 and Kooning et al 5 who found Germ Cell Tumors to Comprised 43.4% and 44% of all ovarian neoplasm respectively. In western world 95% of ovarian Germ cell Tumors are mature cystic teratoma and only 3% of ovarian teratomas are immature.…”
Section: Classes Of Tumor Benign Malignent Border Line Totalcontrasting
confidence: 96%
“…This was different to the findings of Sah et al 8 and Kooning et al 5 who found Germ Cell Tumors to Comprised 43.4% and 44% of all ovarian neoplasm respectively. In western world 95% of ovarian Germ cell Tumors are mature cystic teratoma and only 3% of ovarian teratomas are immature.…”
Section: Classes Of Tumor Benign Malignent Border Line Totalcontrasting
confidence: 96%
“…There were altogether 17 individual derivatives observed in this research work. In our study skin and its appendages were the frequent derivatives, each constituting 98.64%, similar to other studies, whereas it was observed in 100% of the tumors in a case series reported by Ayan et al [4,27]. The dominant mesodermal structures were bone and/or cartilage either or both were detected in 100% of cases [32].…”
Section: Identification Of Germ Layer Derivativessupporting
confidence: 91%
“…Comparing with different other types of germ cell tumors like dysgerminomas, and endodermal sinus tumors, they are most commonly observed. [25][26][27]; and also the most common tumor among all ovarian neoplasms accounting for 40.3% to 42.8% of all ovarian tumors [27][28][29]. The incidence of MCTs during pregnancy was 0.2% among ovarian tumors [17] while the incidence was higher in range of 3% to 3.5% in other series Online…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They may contain skin, hair follicle, and sweat gland, bones, nail and teeth. Dermoid cysts may be asymptomatic or present with abdominal swelling, discomfort, and pain 2,3 and typically occur during reproductive age (mean age, 27 years). 4 Ovarian cysts are labelled as large when they are over 5 cm in diameter and giant voluminous when they exceed 15 cm.…”
Section: Discussionmentioning
confidence: 99%